2014
DOI: 10.1177/0333102414553824
|View full text |Cite
|
Sign up to set email alerts
|

A human capsaicin model to quantitatively assess salivary CGRP secretion

Abstract: Oral application of red chili homogenate is well tolerated and causes a dose-dependent CGRP release in saliva, without day-to-day effects in this response. This model could be used to noninvasively study the activation state of the trigeminal nerve innervating salivary glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Demirbilek et al (2004), for example, observed that subcutaneously administered capsaicin increased plasma CGRP concentration in rats. Oral administration of a red chili homogenate in human subjects also increased CGRP concentration in a dose-dependent manner (van Oosterhout et al, 2015). In the current experiment, RPC may have stimulated CGRP production and decreased insulin secretion.…”
Section: Discussionsupporting
confidence: 49%
“…Demirbilek et al (2004), for example, observed that subcutaneously administered capsaicin increased plasma CGRP concentration in rats. Oral administration of a red chili homogenate in human subjects also increased CGRP concentration in a dose-dependent manner (van Oosterhout et al, 2015). In the current experiment, RPC may have stimulated CGRP production and decreased insulin secretion.…”
Section: Discussionsupporting
confidence: 49%
“…The inhibitory effect of capsaicin on insulin may be exhibited via CGRP, which is known to decrease insulin secretion by the pancreas (Pettersson and Ahrén, 1990;Tanaka et al, 2013). Capsaicin treatments reportedly increased plasma CGRP concentration in rats and human subjects (Demirbilek et al, 2004;van Oosterhout et al, 2015). Hashemzadeh-Cigari et al (2015) reported increased insulin sensitivity in dairy cows fed a mixture of PN including rosemary, cinnamon bark, turmeric, and clove bud.…”
Section: Hormone Regulationmentioning
confidence: 99%
“…It is worth mentioning that these two groups with different capsaicin dosages showed some differences in the CGRP expression levels at 12 h. The mechanism behind this effect might be the dose-dependent release of CGRP induced by excitation of TRPV1 24 . This could also be supported by the observation that application of capsaicin caused a dose-dependent release of salivary CGRP, which might reflect the activated state of trigeminal system 27 . Moreover, in our study, we found that following experimental tooth movement, CGRP expression levels both in TG and Vc at 1 d and 3 d were significantly lower than that in the saline+force group.…”
Section: Discussionmentioning
confidence: 82%